1991
DOI: 10.1021/jm00106a017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity relationship analysis of cation-substituted polyaromatic compounds as potentiators (amplifiers) of bleomycin-mediated degradation of DNA

Abstract: A set of 21 polyheteroaromatic compounds substituted with flexible cationic groups and of similar molecular size has been analyzed for binding with DNA and for effects of the bleomycin-mediated degradation of the DNA double helix. Increases in apparent rates of the DNA digestion were observed in all cases under the experimental conditions of noncompetitive binding of these compounds and bleomycin to DNA. Surprisingly, the quantitative structure-activity relationship analysis revealed two distinct correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…BzP, which also has two unfused rings, was weakly active in yeast but not in the V79 assay. Diverse lines of evidence support the interpretation that BLM enhancement by these compounds can be ascribed to intercalation: results from a structure-based computational DNA docking model Snyder et al, , 2006 Table X); ethidium displacement assays [Snyder, 1998]; enhanced cleavage of DNA in vitro by intercalators [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991; and the finding that enhancement by DPH (Table VIII), tamoxifen (Table IX), or various acridines [Hoffmann et al, 2009] in yeast grown in the presence of intercalating agents occurs for BLM treatments in buffer in the absence of free intercalating agent.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…BzP, which also has two unfused rings, was weakly active in yeast but not in the V79 assay. Diverse lines of evidence support the interpretation that BLM enhancement by these compounds can be ascribed to intercalation: results from a structure-based computational DNA docking model Snyder et al, , 2006 Table X); ethidium displacement assays [Snyder, 1998]; enhanced cleavage of DNA in vitro by intercalators [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991; and the finding that enhancement by DPH (Table VIII), tamoxifen (Table IX), or various acridines [Hoffmann et al, 2009] in yeast grown in the presence of intercalating agents occurs for BLM treatments in buffer in the absence of free intercalating agent.…”
Section: Discussionmentioning
confidence: 91%
“…Studies with isolated DNA had shown that various agents besides classical intercalators with fused heterocyclic rings bind to DNA in a manner consistent with intercalation and enhance the in-vitro degradation of DNA by BLM [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991. Such unconventional intercalators with unfused rings might not be predicted to intercalate into DNA on the basis of visual inspection of chemical structure, but they were found to be active in the BLM amplification assay in Chinese hamster cells [Snyder, 1998[Snyder, , 2007Snyder and Arnone, 2002;Snyder and Brown, 2002;Snyder and Strekowski, 1999;Snyder et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenic, clastogenic, and DNA-damaging effects of BLM were previously reported to be potentiated by acetaldehyde, 3-aminobenzamide, caffeine, ethanol, hydroxyurea, isoptin, hyperthermia [Povirk and Austin, 1991], ␤-carotene [Salvadori et al, 1994;Gentile et al, 1998], heterocyclic aromatic intercalating agents [Strekowski et al, 1991;Snyder, 1998], triethylenetetramine [An and Hsie, 1992], and hyperbaric oxygen [Cederberg and Ramel, 1989]. Agents reported to protect against the genotoxicity of BLM include ascorbic acid, chlorophyllin, galangin, 13-cis-retinoic acid, taurine [Gentile et al, 1998], butylated hydroxytoluene [Grillo and Dulout, 1997], the chelating agent EGTA, Zn ϩ2 [Tempel and Ignatius, 1993], and 4-hydroxy-2,2,6,6,-tetramethylpiperidine-1-oxyl [An and Hsie, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Seeking to identify drugs that would enhance the antitumor activity of the DNA groove-binding drug bleomycin, they discovered that DNA intercalators could alter the topology of a naked DNA molecule in such a way as to enhance the DNA double-strand nicking activity of bleomycin [Strekowski et al, 1987[Strekowski et al, , 1991Wilson et al, 1988Wilson et al, , 1990Strekowski, 1992]. A variety of other mechanisms that could account for bleomycin amplification aside from DNA intercalation were also discussed in these studies.…”
Section: Noncovalent Dna Interactionmentioning
confidence: 99%